Nursing students' experience of approaching risk for suicide behaviour through simulated environments: a content analysis study - Quemada-González, Casta; Becerra-Martos, Elena Flores; Blenkarn, Morgan; Gutiérrez-Rodríguez, Laura del Carmen; García-Mayor, Silvia; León-Campos, Álvaro; Martí-García, Celia (Elsevier, 2024)
Background Suicide is a major public health problem, especially among the young population. Nurses are in a unique position to prevent it due to their constant contact with patients. However, addressing suicidal behaviour can be complicated by the emotional responses it elicits. Simulation has been shown to be an effective tool to increase the self-confidence of nursing students in dealing with these sensitive situations in a safe environment prior to dealing with real patients. Aim To explore nursing students' perceptions, thoughts, and emotions about their performance in dealing with risk for suicidal behaviour through simulated scenarios. Design Qualitative descriptive study. Methods Students of Mental Health and Psychiatric II in the third year of the Nursing course at the University of Málaga were invited to explain their experience by answering a questionnaire of three open-ended questions following their participation in the simulated scenarios of the course. Results A total of 72 students participated. Content analysis of the written responses identified three main themes: (i) Emotions experienced during the simulation; (ii) Self-criticism of the performance/intervention; (iii) Student evaluation of the learning experience. Most of the students indicated at some point during the clinical scenario, they had felt anxiety, proposing possible improvements in their own performance. The clinical scenario that elicited the most negative emotions was that of a person diagnosed with borderline personality disorder. Conclusion Clinical simulations contribute to a better understanding of nursing practice with mental health patients and the need for training in emotional and therapeutic communication skills among students.
Keywords: Enfermería; Estudiantes universitarios; Métodos de simulación; Suicidio; Nursing student; Suicide; Simulation training; Emotions; Nonverbal communication